Cerium‐Complex‐Catalyzed Oxidation of Arylmethanols under Atmospheric Pressure of Dioxygen and Its Mechanism through a Side‐On μ‐Peroxo Dicerium(IV) Complex. Issue 12 (21st January 2016) - Paul, Mitali; Shirase, Satoru; Morimoto, Yuma; Mathey, Laurent; Murugesapandian, Balasubramanian; Tanaka, Shinji; Itoh, Shinobu; Tsurugi, Hayato; Mashima, Kazushi
Abstract: A new Ce IV complex [CeNH(CH2 CH2 N=CHC6 H2 ‐3, 5‐( t Bu)2 ‐2‐O)2 (NO3 )2 ] (1 ), bearing a dianionic pentadentate ligand with an N3 O2 donor set, has been prepared by treating (NH4 )2 Ce(NO3 )6 with the sodium salt of ligandL1 . Complex1 in the presence of TEMPO and 4 Å molecular sieves (MS4 A) has been found to serve as a catalyst for the oxidation of arylmethanols using dioxygen as an oxidant. We propose an oxidation mechanism based on the isolation and reactivity study of a trivalent cerium complex [CeNH(CH2 CH2 N=CHC6 H2 ‐3, 5‐( t Bu)2 ‐2‐O)2 (NO3 )(THF)] (2 ), its side‐on μ‐O2 adduct [CeNH(CH2 CH2 N=CHC6 H2 ‐3, 5‐( t Bu)2 ‐2‐O)2 (NO3 )]2 (μ‐η 2 :η 2 ‐O2 ) (3 ), and the hydroxo‐bridged Ce IV complex [CeNH(CH2 CH2 N=CHC6 H2 ‐3, 5‐( t Bu)2 ‐2‐O)2 (NO3 )]2 (μ‐OH)2 (4 ) as key intermediates during the catalytic cycle. Complex2 was synthesized by reduction of1 with 2, 5‐dimethyl‐1, 4‐bis(trimethylsilyl)‐1, 4‐diazacyclohexadiene. Bubbling O2 into a solution of2 resulted in formation of the peroxo complex3 . This provides the first direct evidence for cerium‐catalyzed oxidation of alcohols under an O2 atmosphere. Abstract : Cerium‐catalyzed alcohol oxidation : A new Ce IV complex [CeNH(CH2 CH2 N=CHC6 H2 ‐3, 5‐( t Bu)2 ‐2‐O)2 (NO3 )2 ] (1 ) has been shown to serve as a catalyst for the oxidation of arylmethanols using dioxygen as an oxidant in the presence of TEMPO and molecular sieves MS4 A (see scheme). Ce III complex2, obtained by reduction of1 with 2, 5‐dimethyl‐1, 4‐bis(trimethylsilyl)‐1, 4‐diazacyclohexadiene, reacted with O2 to give the peroxo complex3 . This provides the first direct evidence for operation of the peroxo mechanism in the cerium‐catalyzed oxidation of alcohols under O2 atmosphere.